Proton beam therapy for children and adolescents and young adults (AYAs): JASTRO and JSPHO Guidelines. (July 2021) - Mizumoto, Masashi; Fuji, Hiroshi; Miyachi, Mitsuru; Soejima, Toshinori; Yamamoto, Tetsuya; Aibe, Norihiro; Demizu, Yusuke; Iwata, Hiromitsu; Hashimoto, Takayuki; Motegi, Atsushi; Kawamura, Atsufumi; Terashima, Keita; et al.
Highlights: The JASTRO and JSPHO jointly developed the Guidelines for PBT in children and AYA patients. Based on in silico analysis, PBT decreases the doses to normal tissues and risks for second cancer in patients with childhood cancer who undergo CSI. PBT for childhood tumor, was confirmed to have better cost-effectiveness due to reduced adverse events. Clinical questions were prepared based on studies of PBT for major pediatric solid cancers, including brain tumors, and a systematic review was conducted. Abstract: Children and adolescents and young adults (AYAs) with cancer are often treated with a multidisciplinary approach. This includes use of radiotherapy, which is important for local control, but may also cause adverse events in the long term, including second cancer. The risks for limited growth and development, endocrine dysfunction, reduced fertility and second cancer in children and AYAs are reduced by proton beam therapy (PBT), which has a dose distribution that decreases irradiation of normal organs while still targeting the tumor. To define the outcomes and characteristics of PBT in cancer treatment in pediatric and AYA patients, this document was developed by the Japanese Society for Radiation Oncology (JASTRO) and the Japanese Society of Pediatric Hematology/Oncology (JSPHO).